Dynamic stability of fcc crystals under isotropic loading from first principles - Rehák, Petr; Cerný, Miroslav; Pokluda, Jaroslav (Journal of physics. Condensed matter, 2012)
Lattice dynamics and stability of four fcc crystals (Al, Ir, Pt and Au) under isotropic (hydrostatic) tensile loading are studied from first principles using the linear response method and the harmonic approximation. The results reveal that, contrary to former expectations, strengths of all the studied crystals are limited by instabilities related to soft phonons with finite or vanishing wavevectors. The critical strains associated with such instabilities are remarkably lower than those related to the volumetric instability. On the other hand, the corresponding reduction of the tensile strength is by 20% at the most. An analysis of elastic stability conditions is also performed and the results obtained by means of both approaches are compared.
Keywords: mechanický stres; Metals; Computer Simulation; chemické modely; Anisotropy; Models, Chemical; Stress, Mechanical; Crystallization; krystalizace; Tensile Strength; anizotropie; počítačová simulace; kovy; pevnost v tahu